Flores e pinturas na paisagem: análise espacial e intra-sítio em Campo das Flores - Valdinêy Amaral Leite (2016)
Field of Flowers is located in the Araçuaí River basin, between the municipalities Senador Modestino Gonçalves and Itamarandiba-MG in Upper Jequitinhonha. This research had the concern investigate the relations which we can weave between sites with rock record; between the painted and unpainted supports. It sought to observe if there was choices or pattern (s) of insertion of these sites in the landscape and if they were occupied diachronically or synchronically in space.To cater the proposed objective, embarked if on flowing archeology of the landscape, addressing the area of spatial form (inter-site) and at the same intra-site time, it was observed the particularities of each site and also the potential places that seemingly show no visible rock records today, but that may have been occupied or participated in 'selective processes' of which place to paint. The methodology used, if endorses in intensive fieldwork, application of analysis tokens, plastic calque, consultation the literature, image processing in CorelDraw®, data processing in SPSS and cartographic surveys through the ArcGis®. The results obtained in this dissertation it is intended to offer information of the local archeology, to the communities that are there and join forces with other research that has been developed in this area by LAEP / UFVJM and by the UFMG Archaeology Sector in the region of Diamantina-MG.